Serum N-terminal Pro-B-type Natriuretic Peptide Predicts Mortality in Cardiac Surgery Patients Receiving Renal Replacement Therapy - Su, Ying; Hou, Jun-yi; Zhang, Yi-jie; Ma, Guo-guang; Hao, Guang-wei; Luo, Jing-chao; Luo, Zhe; Tu, Guo-wei (Frontiers in Medicine, 2020)
Background: N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a useful cardiac biomarker that associates with acute kidney injury (AKI) and mortality after cardiac surgery. However, its prognostic value in cardiac surgical patients receiving renal replacement therapy (RRT) remains unclear. Objectives: Our study aimed to assess the prognostic utility of NT-proBNP in patients with established AKI receiving RRT after cardiac surgery. Methods: A total of 163 cardiac surgical patients with AKI requiring RRT were enrolled in this study. Baseline characteristics, hemodynamic variables at RRT initiation and NT-proBNP level before operation, at RRT initiation and on the first day after RRT initiation for each patient were prospectively collected. The primary outcome was 28-day mortality after RRT initiation. Results: Serum NT-proBNP level in non-survivors was significantly higher than survivors at pre-operation (4096[962.0,9583.8] vs. 1339[446,5173] pg/mL; P＜0.01), RRT initiation (10366[5668,20646] vs. 3779[1799,11256] pg/mL; P＜0.001) and the first day after RRT initiation (9055.0[4392,24348] vs. 5255[2134,9175] pg/mL; P＜0.001). The area under the receiver operating characteristic curve of NT-proBNP for predicting 28-day mortality was 0.64 (0.55-0.73), 0.71 (0.63-0.79) and 0.68 (0.60-0.76), respectively. Consistently, Cox proportional hazards regression revealed that NT-proBNP levels (with log transformation) in pre-operation (HR 1.27; 1.06-1.52), at RRT initiation (HR 1.11; 1.06-1.17) and on the first day after RRT initiation (HR 1.17; 1.11-1.23) were independently associated with 28-day mortality. Conclusions: Serum NT-proBNP was an independent predictor of 28-day mortality in cardiac surgical patients with AKI requiring RRT. The prognostic role of NT-proBNP needs to be warranted in future.